METHODS OF INCREASING THE INTERFERENCE OF HIGH-SPEED CHANNELS OF DATA TRANSMISSION OF UNMANNED SURFACE VEHICLE - Evgeny A. Zhivilo (Sučasnì Informacìjnì Tehnologìï u Sferì Bezpeki ta Oboroni)
Protection of the underwater space within the territorial sea of Ukraine is one of the functions of the Armed Forces of Ukraine. Responsibility for the exercise of these functions lies directly with the Naval Forces of the Armed Forces of Ukraine. The illumination of the situation in the underwater space is one of the tasks for the Navy's ships, the successful solution of which contributes to the functions of ensuring the protection of the underwater space, increasing the protection of ships from underwater threats in the parking lots and during tasks in less dangerous areas. In order to perform these functions, the article analyzes the two-step method of additional gating of analogue-digital converter counters during I / Q-demodulation of OFDM signals, and more significantly different way of additional gating of digital signal counts in a "sliding window" mode is offered.  The above proposals can be used as a basis for further scientific research on the development of the theory of digital signal processing, as well as in the production of digital segments of control systems and communication complexes of small scale surface vessels based on modern technologies.